ANALISIS TINGKAT BAHAYA EROSI SUB DAERAH ALIRAN SUNGAI TAPUNG KANAN - Sutrisna Sutrisna; Aras Mulyadi; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2014)
The research on erosion level (TBE) in the sub watershed of Tapung kanan has beenconducted on February-March 2013 using the USLE (Universal Soil Loss Equation) bythe formula A = RxKxLSxC.P. The results showed that the change of use / land coverimpact on the actual increase in the level of erosion that occurs in each type of landuse. Erosion hazard level (TBE) which occurs in the sub watershed of Tapung Kanan,for each type of use / land cover has a magnitude which varies, with an average erosionrate of 130.18 tons / Ha / year, and the distribution for each class TBE is: very Low(SR): 16986.50 Ha (7.17)%; Low: 35343.73 ha (14.92%); Moderate: 142,155.01 ha(60.01%); high: 32109.48 Ha (13.55%) and very high: 10290.71 ha (4.34%). TSL valueof Tapung Kanan Sub watershed which obtained from this research ranged from 14.40-30.00 tons / ha / year, while the average value of the actual erosion of 130.14 tons / ha/ year, thus the Erosion hazard level of Tapung kanan Sub Watershed exceeds thepermitted threshold, the SDR value of 0.463, still below the SDR standard value of0.490.